2010
DOI: 10.5198/jtlu.v2i3.23
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the commuting network in Germany: Spatial and connectivity patterns

Abstract: Abstract:e analysis of the structure and evolution of complex networks has recently received considerable attention. Although research on networks originated in mathematical studies dating back to the nineteenth century (or earlier), and developed further in the mid-twentieth century with contributions to graph theory, interest in its application to the social sciences is currently growing-particularly in regional science and transportation, because of the spatial relevance of networks. is paper presents a dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Consequently, we might conjecture an 'intermediate' structure between homogeneous and heterogeneous configurations for the trip-makers (see Section 2). In addition, given recent results which highlight the polarization characteristics of the German commuting flows in the year 2005 (Patuelli et al 2007(Patuelli et al , 2010, we may infer here a tendency towards heterogeneity/ polarization in the commuter flows between the German districts.…”
Section: Impedance Function Based On Observed Datamentioning
confidence: 90%
See 1 more Smart Citation
“…Consequently, we might conjecture an 'intermediate' structure between homogeneous and heterogeneous configurations for the trip-makers (see Section 2). In addition, given recent results which highlight the polarization characteristics of the German commuting flows in the year 2005 (Patuelli et al 2007(Patuelli et al , 2010, we may infer here a tendency towards heterogeneity/ polarization in the commuter flows between the German districts.…”
Section: Impedance Function Based On Observed Datamentioning
confidence: 90%
“…Good reviews on this topic can be found in, amongst others, Barabási and Oltvai (2004), Grubesic et al (2008), and Jeong et al (2003). Recent applications in transport concern the identification of an RN vs. an SF network with reference to the evolution of commuting flows (De Montis et al 2007;Patuelli et al 2010;Russo et al 2007), and of air transport flows (Barrat et al 2004;Reggiani et al 2010a).…”
Section: Network Models: a Brief Reviewmentioning
confidence: 97%
“…In the last decade, the field of distributed processing of large-scale graphs has attracted considerable attention [5]. This attention has been motivated not only by the increasing size of graph data, but also by its huge number of applications, such as the analysis of social networks [8], web graphs [2] and spatial networks [18]. In this context, many distributed/parallel graph processing systems have been proposed, such as Pregel [16], GraphLab [15], and Trinity [23].…”
Section: Introductionmentioning
confidence: 99%
“…Patuelli et al (2010) conducted an analysis of German commuting trends from both a spatial and network perspective to understand the hierarchies among 439 German districts. Zhang et al (2012) analyzed the association between road network structure and nonmotorist safety using data from census tracts in Alameda County, California.…”
Section: Network Structurementioning
confidence: 99%